Atomistic Insights Into Lubricated Tungsten/Diamond Sliding Contacts - Romero, Pedro A.; Mayrhofer, Leonhard; Stoyanov, Pantcho; Merz, Rolf; Kopnarski, Michael; Dienwiebel, Martin; Moseler, Michael (Frontiers in Mechanical Engineering, 2019)
The reinforcement of coatings with diamond particles results in superior tribological performance for automotive applications. In addition to improving the coating’s bulk properties, sliding of diamond on metallic counter bodies contributes to improved tribological performance. Therefore, in order to design better diamond reinforced coatings, it is imperative to understand the atomistic mechanisms at sliding metal/diamond interfaces. Here, we investigate the interfacial tribo-chemical mechanisms leading to low friction in lubricated tungsten/diamond sliding contacts by combining reactive atomistic simulations with on-line tribometry experiments linked to chemical analysis. Reactive classical molecular dynamics simulations reveal the dehydrogenation of hexadecane lubricant molecules between tungsten/diamond contacts by proton transfer from the hexadecane to octahedral sites of the tungsten surface. Subsequent chemisorption of the radicalized hexadecane on dangling C-bond sites of the diamond surface leads to the formation of low-density hydrocarbon films, which significantly lower frictional resistance in the tribo-contact. Quasi-static density functional theory calculations confirm the classical molecular dynamics results and reveal that radicalized hydrocarbon molecules can also bond via C-O bonds on a WO3 layer covering the tungsten counter surface. The on-line tribometry experiments confirm the reduction of friction under hexadecane lubrication and ex situ chemical analysis by means of XPS, AES and EELS provide evidence of the formation of a carbon-rich tribofilm on the diamond and tungsten-oxide surfaces as predicted by the atomistic simulations.